SIMULATION OF MONOCOQUE CHASSIS STRUCTURE OF ELECTRIC VEHICLES BASED ON COMPOSITE MATERIALS - Daryono, Daryono; Yusvana, Bima Fatureza; Saifullah, Ali (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
The chassis is one of the main components in a prototype electric motor vehicle, serving as the structural support for the drivetrain, steering system, and driver safety. This study aims to design and simulate a monocoque composite chassis as an alternative to the conventional ladder frame. The methodology employed finite element analysis using Ansys Composite Pre-Post (ACP) to define ply details, orientation, and laminate thickness. The materials used were Epoxy Unidirectional Carbon Fiber, Epoxy Carbon Woven, and PVC Foam as the core. The simulation results indicate that the chassis experienced a maximum deformation of 0.8933 mm, a maximum principal stress of 34.53 MPa, and a maximum principal elastic strain of 0.001028 mm/mm. The composite failure criterion value of 0.2666 (< 1) shows that the structure remains in a safe condition. Furthermore, the monocoque design successfully reduced the mass by 3.1 kg compared to the previous chassis, supporting improved vehicle efficiency. Overall, this study demonstrates that the monocoque composite chassis design provides a better combination of strength, stiffness, and mass efficiency compared to the ladder frame and has strong potential for application in the development of prototype electric motor vehicles.